REFORMASI BIROKRASI DI UPT PERTANIAN DAN KETAHANAN PANGAN WILAYAH KECAMATAN JATINUNGGAL KABUPATEN SUMEDANG - Yayat Ruhiyat (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2019)
This study aims to obtain a description of Bureaucratic Reform in Upt Agriculture and Food Security in Jatinunggal District, Sumedang District The research method used is qualitative with a descriptive approach. The research informants consisted of the head of Upt agriculture, head of administration, head of the program, secretary of the department of agriculture and food security, staff in the field of agricultural statistics, agricultural extension workers. Data collection techniques are carried out through literature studies and field studies consisting of interviews, observation and documentation. Data analysis was performed by data reduction, data presentation, drawing conclusions and combinations. The results of this study that the bureaucratic reform in Upt Agriculture and Food Security District Jatinunggal District Sumedang Regency: First, supported by organizational culture, which is still less conducive this can be seen in the observations of researchers who say that the leader in this case the leader is still acting authoritarian. Another supporting factor is the effectiveness of the Organizational Structure, as a whole the services at the UPT Agriculture and Food Security in Jatinunggal District are run with the current operational standard procedures, but there are several types of services that still have not been made SOPs such as convenience for beneficiaries in accessing services through the chart / service flow that actually provides information on the service process to be taken. Other factors Employee welfare with employee welfare or compensation is good and maximum, employees can get a number of things including work motivation, work loyalty, physical and mental health that is maintained, as well as strengthening relationships and work relationships between employees. Therefore the welfare of employees for every employee both civil servants and non-civil servants is required that the organizational goals of the Agricultural and Food Security Unit of Jatinunggal District be achieved. Other supporting factors are responsibility, the overall way to shape culture is to determine action steps, provide space for